27‐4: Organic Light‐Emitting Diodes with Directional Polarized Light Emission. Issue 1 (28th June 2021) - Fu, Xiangyu; Zhu, Liping; Mehta, Yash; Chen, Yi-An; Lei, Lei; Barange, Nilesh; Dong, Qi; Yin, Shichen; Mendes, Juliana; He, Siliang; Gogusetti, Renuka; Chang, Chih-Hao; et al.
Abstract : Organic light emitting diodes (OLEDs) with directional and polarized light emission have many photonic applications, and beam shaping of these devices is fundamentally challenging because they are Lambertian light sources. In this work, using OLEDs for demonstrations, by selectively diffracting the TE waveguide mode while suppressing other optical modes in a nanostructured substrate, we demonstrated highly directional light emission from a full‐area OLED with a small divergence angle less than 3°, and a TE to TM polarization extinction ratio of 13. The highly selective diffraction of only the TE waveguide mode is possible due to the planarization of the device stack by thermal evaporation and solution processing.